Telemedicine And Consumer Protection Ensuring Patient Privacy and Safety in A Digital Healthcare Landscape - Savitha.K, Savitha.K; Sharmila, M.S. (Journal of Neonatal Surgery, 2025)
This research provides a comprehensive overview of telemedicine within the Indian healthcare sector, emphasizing the necessity for a robust legal framework that ensures safety, security, and consumer privacy. This study particularly highlights the communication gap between healthcare practitioners and patients. Additionally, it seeks to understand the challenges faced by the physicians in utilizing digital tools for registration and treatment delivery. Furthermore, this research examines the effectiveness of existing telemedicine guidelines and the potential for misuse of its benefits. It underscores the importance of preventive and protective measures while also analysing the legal and ethical dimensions of telemedicine practice, as outlined in the Indian Medical Council’s Regulations on Professional Conduct, Etiquette, and Ethics (2002). The absence of comprehensive data protection legislation in India complicates efforts to secure patient data effectively, emphasizing the need for enforceable laws to safeguard privacy. This research also proposes the enactment of legislation for the protection of patient data in telemedicine